Burrow/Intensity Fluctuation of Field Rodents in Relation to the Development Stages of Vegetable Crops - Kumar, Parmesh; Pashan, S C; Sabhlok, V P; Singhal, R K (Annals of Arid Zone, 2016)
Fluctuations in burrow intensity of sympatric field murids in relationto the development stages of four sunUller vegetable crops, viz., bottle gourd, musk melon, sponge gourd and cucumber were recorded to be minimum at seedling stage (avemge, 5.50±